Ro membrane filter element and production process thereof
By depositing a sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating on the polyamide reverse osmosis membrane, the problem of insufficient anti-pollution performance of the membrane when facing a variety of pollutants is solved, and more efficient water purification and longer service life are achieved.
Patent Information
- Application Number
- CN202411977189.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When facing organic and inorganic pollutants in raw water, the polyamide reverse osmosis membrane has insufficient anti-pollution performance, resulting in the efficient operation of the membrane being hindered.
An aromatic polyamide film with sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating was used to form a stable coating to improve the film's anti-pollution performance through co-deposition of polydopamine and zwitterionic polymer and Michael addition reaction of sulfated polyglycidyl ether.
It significantly improves the anti-biological and inorganic pollution properties of the RO membrane, extends the service life of the membrane, and enhances its durability.
Smart Images

Figure BDA0005220711190000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of reverse osmosis (RO) membranes, and more specifically, to a RO membrane filter element and a production process thereof. Background Art
[0002] Reverse osmosis membrane (RO membrane) is a semi-permeable membrane with specific properties that is artificially synthesized. This membrane allows solvents to pass through, but solutes cannot pass through. It is the core component of reverse osmosis technology. The surface pore size of the reverse osmosis membrane is very small, ranging from 0.5-10nm, which can effectively remove various pollutants in the water, including microorganisms, salts, etc., thereby achieving the effect of purifying water quality.
[0003] Polyamide reverse osmosis membrane is one of the mainstream RO membranes in membrane water treatment, and polyamide reverse osmosis membrane is mainly aromatic polyamide membrane. The molecular chain skeleton of aromatic polyamide membrane material is composed of alternating benzene rings and amide groups. The presence of benzene rings restricts the internal rotation of the molecular chain in the system, and the molecular chains form hydrogen bonds due to the presence of highly polar amide groups, thereby enhancing the interaction between the molecular chains, and thus promoting the aromatic polyamide reverse osmosis membrane to have extremely excellent permeation selectivity and stability.
[0004] However, although polyamide reverse osmosis membranes have the advantages of high water flux, high salt rejection rate, high stability, etc., polyamide reverse osmosis membranes are still often affected by organic pollutants, inorganic pollutants and biological contamination in raw water, thus hindering the efficient operation of polyamide reverse osmosis membranes. Summary of the invention
[0005] In order to improve the defect of poor anti-pollution performance of conventional aromatic polyamide reverse osmosis membrane, the present application provides a RO membrane filter element and a production process thereof.
[0006] In the first aspect, the present application provides a ro membrane filter element, which adopts the following technical solution:
[0007] The invention discloses a RO membrane filter element, which is an aromatic polyamide membrane with a sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating deposited on the surface.
[0008] Sulfated polyglycidyl ether is a polymer with a three-dimensional dendritic structure, which has excellent hydrophilicity, good protein and bacteria repellency, excellent thermal stability and excellent chemical stability. Therefore, when sulfated polyglycidyl ether is deposited on the RO membrane, the RO membrane will have extremely good anti-biological pollution performance. However, when sulfated polyglycidyl ether is deposited on the RO membrane, its anti-inorganic pollution performance is still insufficient.
[0009] The attachment of inorganic pollutants on the surface of RO membrane is mainly caused by the hydrophobic-hydrophobic interaction between the membrane and the pollutants. Therefore, hydrophilic modification of RO membrane is one of the important methods to improve the anti-fouling performance of RO membrane. Zwitterionic polymer is a polymer containing both positively charged and negatively charged groups. The hydrophilic groups it contains can form hydrogen bonds in water and interact with water molecules to obtain extremely good hydrophilicity. Therefore, when zwitterionic polymer is deposited on RO membrane, RO membrane will have extremely good anti-fouling performance.
[0010] However, both sulfated polyglycidyl ether and zwitterionic polymer have relatively poor connection effects with aromatic polyamide membranes, resulting in a short anti-fouling performance of RO membranes. Polydopamine coating has the advantages of simple preparation, wide applicable substrate range and strong adhesion ability, and polydopamine can also be co-deposited with zwitterionic polymers, thereby stably connecting zwitterionic polymers to the surface of aromatic polyamide membranes, and sulfated polyglycidyl ether can be grafted onto polydopamine coatings through Michael addition reaction, thereby forming a stable sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating on the aromatic polyamide membrane.
[0011] In addition, during the long-term use of the RO membrane, micro-damage to the polydopamine coating is likely to lead to further adhesion and proliferation of pollutants, and enabling the polydopamine coating to have a self-healing function can effectively improve the above problems.
[0012] Self-repairing includes autonomous self-repairing and non-autonomous self-repairing. Autonomous self-repairing does not require any additional external triggers. The destruction itself is the stimulus for self-repairing, and the repair process is carried out autonomously within the material structure. In order to enable the polymer to form a self-repairing function, non-covalent bonds such as hydrogen bonds, ionic interactions or metal-ligand interactions and reversible covalent bonds such as disulfide bonds or acylhydrazone bonds are usually introduced into the polymer. The sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating has reversible covalent bonds, disulfide bonds, non-covalent bonds such as ionic interactions, and metal-ligand interactions, which enables the sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating to have certain self-repairing properties, thereby obtaining better durability.
[0013] Preferably, the sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating is formed by the reaction of dopamine hydrochloride, sulfated polyglycidyl ether and zwitterionic polymer, and the mass ratio of dopamine hydrochloride, sulfated polyglycidyl ether and zwitterionic polymer is 1 (4-6):1.
[0014] When dopamine hydrochloride, sulfated polyglycidyl ether and zwitterionic polymer adopt the above mass ratio, the prepared sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating will be more stable, thereby enabling the RO membrane to have better anti-fouling performance.
[0015] Preferably, the preparation method of the sulfated glycidyl ether comprises the following steps:
[0016] Preparation of polyglycidyl ether: 170-190 mg 1,1,1-tri(hydroxymethyl)ethane, 20-30 mg sodium formate and 1-3 ml anhydrous methanol are stirred at room temperature for 1-3 h, 1,1,1-tri(hydroxymethyl)ethane is deprotonated by 10%, and then methanol is removed under vacuum at 70-90° C., then 30-50 ml 1,4-dioxane is added, ultrasonic dispersion is performed, argon is introduced to remove dissolved oxygen, and then 15-25 ml of a mixture of glycidol and 1,4-dioxane is slowly dripped in, the volume ratio of glycidol to 1,4-dioxane is 1:1, and after the dripping is completed, the reaction is continued at 90-110° C. for 12 h. After the reaction is completed, it is first cooled to room temperature, 1,4-dioxane is poured out, methanol is added to dissolve the polymer, the polymer is precipitated with excess n-hexane, and then vacuum dried to obtain polyglycidyl ether;
[0017] Preparation of α-lipoic acid-polyglycidyl ether: 8-10 g of polyglycidyl ether was dissolved in 50-70 ml of N,N-dimethylformamide, and then 0.7-0.9 g of α-lipoic acid, 0.7-0.8 g of 4-(N,N-dimethylamino)pyridine and 0.7-0.9 g of N,N'-dicyclohexylcarbodiimide were added in turn under ice bath conditions, and reacted at room temperature for 35 h. The crude product was then precipitated with ether and dialyzed, and lyophilized to obtain α-lipoic acid-polyglycidyl ether;
[0018] Preparation of sulfated glycidyl ether: 5-7g α-lipoic acid-polyglycidyl ether is dissolved in 40-60ml N,N-dimethylformamide, and then 13-15g aminosulfonic acid is added, and the reaction is carried out at 80-100°C for 72h. Subsequently, the crude product is precipitated out by ether and dialyzed. After freeze-drying, 12-13g of the product is dissolved in 90-110ml deionized water, and argon is passed for 30min. Then 400-500mg DL-dithiothreitol is added, and the reaction is carried out at 40-60°C for 24h. Finally, it is dialyzed and lyophilized to obtain sulfated glycidyl ether.
[0019] Preferably, the preparation method of the zwitterionic polymer is: dissolving 0.05-0.15g chitosan in 30-50ml 1% acetic acid solution, then heating to 50-70°C while introducing nitrogen, adding 20-30mg ammonium persulfate initiator and 0.4-0.6g 2-methacryloyloxyethyl phosphorylcholine in sequence, reacting at a temperature of 50-70°C for 12h, then cooling to room temperature, dialyzing, concentrating and freeze-drying to obtain a zwitterionic polymer.
[0020] Preferably, gallium nitrate and ammonium persulfate are added during the preparation of the sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating.
[0021] Preferably, the mass ratio of gallium nitrate to ammonium persulfate is 1:(3-5).
[0022] During the preparation of sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating, the polydopamine coating has the defect of slow deposition speed. After adding gallium nitrate and ammonium persulfate, the ammonium persulfate firstly decomposes rapidly under the catalysis of gallium ions to produce SO 4- Free radicals, SO 4- Free radicals further accelerate the oxidative polymerization of dopamine and increase the deposition rate of polydopamine, thereby achieving rapid preparation of polydopamine coatings. At the same time, the loading of gallium ions also enables the sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating to obtain better antibacterial properties.
[0023] In a second aspect, the present application provides a method for preparing a ro membrane filter element, using the following technical solution:
[0024] A method for preparing a ro membrane filter element comprises the following steps:
[0025] Polyglycidyl ether-polydopamine modification: first, the aromatic polyamide membrane is immersed in a Tris buffer solution of dopamine hydrochloride, reacted at room temperature for 3-5 hours, taken out, blown dry with nitrogen, and then immersed again in a sulfated glycidyl ether solution containing 1wt% triethanolamine and reacted at room temperature for 10-14 hours, then rinsed with deionized water, blown dry with nitrogen, to obtain a polyglycidyl ether-polydopamine modified aromatic polyamide membrane;
[0026] Preparation of RO membrane filter element: soak the polyglycidyl ether-polydopamine modified aromatic polyamide membrane in a zwitterionic polymer aqueous solution and react at room temperature for 20-28 hours, then rinse with anhydrous ethanol and blow dry with nitrogen to obtain a RO membrane filter element.
[0027] Preferably, the concentration of the dopamine hydrochloride Tris buffer is 1.8-2.2 mg / ml; the concentration of the sulfated glycidyl ether solution is 9-11 mg / ml; and the concentration of the zwitterionic polymer aqueous solution is 1.8-2.2 mg / ml.
[0028] When the Tris buffer of dopamine hydrochloride, the sulfated polyglycidyl ether solution and the zwitterionic polymer aqueous solution adopt the above concentrations, the prepared sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating will be more stable, thereby enabling the RO membrane to have better anti-fouling performance.
[0029] Preferably, the specific steps of the polyglycidyl ether-polydopamine modification are:
[0030] First, 5-7 mg of ammonium nitrate and 23-25 mg of ammonium persulfate are added to 5 ml of Tris buffer containing dopamine hydrochloride at a concentration of 1.8-2.2 mg / ml, and then the aromatic polyamide membrane is immersed in the above solution, reacted at room temperature for 3-5 hours, taken out, blown dry with nitrogen, and then immersed again in a sulfated glycidyl ether solution containing 1 wt% triethanolamine at a concentration of 9-11 mg / ml and reacted at room temperature for 10-14 hours, then rinsed with deionized water, blown dry with nitrogen to obtain a polyglycidyl ether-polydopamine modified aromatic polyamide membrane.
[0031] In summary, this application has the following beneficial effects:
[0032] 1. Sulfated polyglycidyl ether is a polymer with a three-dimensional dendritic structure, which has excellent hydrophilic properties, good protein and bacterial repellency, excellent thermal stability and excellent chemical stability. Therefore, when sulfated polyglycidyl ether is deposited on the RO membrane, the RO membrane will have extremely good anti-biological fouling performance.
[0033] 2. However, when sulfated polyglycidyl ether is deposited on the RO membrane, its resistance to inorganic pollution is still insufficient. The attachment of inorganic pollutants on the surface of the RO membrane is mainly caused by the hydrophobic-hydrophobic interaction between the membrane and the pollutants. Therefore, hydrophilic modification of the RO membrane is one of the important methods to improve the anti-pollution performance of the RO membrane. Zwitterionic polymer is a polymer containing both positive and negative charged groups. The hydrophilic groups it contains can form hydrogen bonds in water and interact with water molecules to obtain extremely good hydrophilicity. Therefore, when zwitterionic polymer is deposited on the RO membrane, the RO membrane will have extremely good anti-fouling performance.
[0034] 3. However, both sulfated polyglycidyl ether and zwitterionic polymer have relatively poor connection effects with aromatic polyamide membranes, resulting in a short anti-fouling performance of RO membranes;
[0035] The polydopamine coating has the advantages of simple preparation, wide applicable substrate range and strong adhesion ability. In addition, polydopamine can be co-deposited with zwitterionic polymers, thereby stably connecting the zwitterionic polymers to the surface of the aromatic polyamide membrane. The sulfated polyglycidyl ether can be grafted onto the polydopamine coating through the Michael addition reaction, thereby forming a stable sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating on the aromatic polyamide membrane.
[0036] 4. In addition, during the long-term use of the RO membrane, micro-damage to the polydopamine coating is likely to lead to further adhesion and proliferation of pollutants, and promoting the self-repair function of the polydopamine coating can effectively improve the above problems;
[0037] In order to enable the polymer to form a self-healing function, non-covalent bonds such as hydrogen bonds, ionic interactions or metal-ligand interactions and reversible covalent bonds such as disulfide bonds or acylhydrazone bonds are usually introduced into the polymer. The sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating has reversible covalent bonds, disulfide bonds, non-covalent bonds such as ionic interactions, and metal-ligand interactions, which enables the sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating to have certain self-healing properties, thereby obtaining better durability. DETAILED DESCRIPTION
[0038] The present application is further described in detail below in conjunction with Examples 1 to 6 and Comparative Examples 1 to 3.
[0039] raw material
[0040] 1,1,1-Tris(hydroxymethyl)ethane, sodium formate, α-lipoic acid, 4-(N,N-dimethylamino)pyridine, N,N'-dicyclohexylcarbodiimide, aminosulfonic acid, DL-dithiothreitol, Tris buffer
[0041] and glycidol were purchased from Sigma-Aldrich;
[0042] n-Hexane, 1,4-dioxane, and N,N-dimethylformamide were purchased from Meck;
[0043] Gallium nitrate, dopamine hydrochloride, and 2-methacryloyloxyethyl phosphorylcholine were purchased from MACKLIN;
[0044] Methanol, ether, ammonium persulfate, triethanolamine, and ethanol were purchased from Sinopharm Group;
[0045] Acetic acid damao; chitosan hailongyuan bio; aromatic polyamide membrane Huitong 4040.
[0046] Example 1
[0047] The invention discloses a RO membrane filter element, which is an aromatic polyamide membrane with a sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating deposited on the surface.
[0048] The preparation method of the RO membrane filter element comprises the following steps:
[0049] Polyglycidyl ether-polydopamine modification: first, the aromatic polyamide membrane was immersed in a Tris buffer solution of dopamine hydrochloride, reacted at room temperature for 4 hours, taken out, and dried with nitrogen, and then immersed again in a sulfated glycidyl ether solution containing 1wt% triethanolamine and reacted at room temperature for 12 hours, then rinsed with deionized water, and dried with nitrogen to obtain a polyglycidyl ether-polydopamine modified aromatic polyamide membrane;
[0050] It should be noted that the soaking in this application means that the solution can completely immerse the RO membrane, that is, the solution is excessive;
[0051] Preparation of RO membrane filter element: soak the polyglycidyl ether-polydopamine modified aromatic polyamide membrane in a zwitterionic polymer aqueous solution and react at room temperature for 24 hours, then rinse with anhydrous ethanol and blow dry with nitrogen to obtain a RO membrane filter element;
[0052] The concentration of dopamine hydrochloride in Tris buffer is 2 mg / ml; the concentration of sulfated glycidyl ether solution is 10 mg / ml; and the concentration of zwitterionic polymer aqueous solution is 2 mg / ml.
[0053] The preparation method of sulfated glycidyl ether comprises the following steps:
[0054] Preparation of polyglycidyl ether: 180 mg 1,1,1-tri(hydroxymethyl)ethane, 25 mg sodium formate and 2 ml anhydrous methanol were stirred at room temperature for 2 h, 1,1,1-tri(hydroxymethyl)ethane was deprotonated by 10%, and then methanol was removed under vacuum at 80°C, and then 40 ml 1,4-dioxane was added, ultrasonic dispersion was performed, argon was introduced to remove dissolved oxygen, and then 20 ml of a mixture of glycidol and 1,4-dioxane was slowly dripped in, the volume ratio of glycidol to 1,4-dioxane was 1:1, and the reaction was continued at 100°C for 12 h. After the reaction was completed, it was first cooled to room temperature, 1,4-dioxane was poured out, methanol was added to dissolve the polymer, the polymer was precipitated with excess n-hexane, and then vacuum dried to obtain polyglycidyl ether;
[0055] Preparation of α-lipoic acid-polyglycidyl ether: 9 g of polyglycidyl ether was dissolved in 60 ml of N,N-dimethylformamide, and then 0.8 g of α-lipoic acid, 0.75 g of 4-(N,N-dimethylamino)pyridine and 0.8 g of N,N'-dicyclohexylcarbodiimide were added in turn under ice bath conditions, and reacted at room temperature for 35 h. The crude product was then precipitated with ether and dialyzed, and lyophilized to obtain α-lipoic acid-polyglycidyl ether;
[0056] Preparation of sulfated glycidyl ether: 6g of α-lipoic acid-polyglycidyl ether was dissolved in 50ml of N,N-dimethylformamide, and then 14g of aminosulfonic acid was added, and the reaction was carried out at 90°C for 72h. Subsequently, the crude product was precipitated out by ether and dialyzed. After freeze-drying, 12.5g of the product was dissolved in 100ml of deionized water, and argon was passed for 30min. Then 450mg of DL-dithiothreitol was added, and the reaction was carried out at 50°C for 24h. Finally, it was dialyzed and lyophilized to obtain sulfated glycidyl ether.
[0057] The preparation method of the zwitterionic polymer is as follows: 0.1 g of chitosan is dissolved in 40 ml of 1% acetic acid solution, then heated to 60° C. while introducing nitrogen, 25 mg of ammonium persulfate initiator and 0.5 g of 2-methacryloyloxyethyl phosphorylcholine are added in sequence, the reaction is continued at 60° C. for 12 hours, then cooled to room temperature, dialyzed, concentrated and freeze-dried to obtain the zwitterionic polymer.
[0058] Example 2-Example 3
[0059] The difference from Example 1 is that the concentrations of the dopamine hydrochloride Tris buffer, the sulfated glycidyl ether solution and the zwitterionic polymer aqueous solution are different, as shown in Table 1.
[0060] Table 1 Concentration of components of RO membrane filter element of Example 1-Example 3
[0061]
[0062] Example 4
[0063] The difference from Example 1 is that gallium nitrate and ammonium persulfate are also added to the polyglycidyl ether-polydopamine modification;
[0064] The specific steps are as follows:
[0065] First, 6 mg of ammonium nitrate and 24 mg of ammonium persulfate were added to 5 ml of Tris buffer containing dopamine hydrochloride at a concentration of 2 mg / ml. The aromatic polyamide membrane was then immersed in the above solution, reacted at room temperature for 4 hours, taken out, and blown dry with nitrogen. Then, it was immersed again in a sulfated glycidyl ether solution containing 1 wt% triethanolamine at a concentration of 10 mg / ml and reacted at room temperature for 12 hours. After that, it was rinsed with deionized water and blown dry with nitrogen to obtain a polyglycidyl ether-polydopamine modified aromatic polyamide membrane.
[0066] Example 5-Example 6
[0067] The difference from Example 4 is that the added amounts of gallium nitrate and ammonium persulfate are different, as shown in Table 2.
[0068] Table 2 Addition amount of gallium nitrate and ammonium persulfate in Example 4-Example 6 / mg
[0069] Example 4 Example 5 Example 6 Gallium nitrate 6 5 7 Ammonium sulfate 24 25 23
[0070] Comparative Example 1
[0071] A ro membrane filter element, which is only an aromatic polyamide membrane.
[0072] Comparative Example 2
[0073] The difference from Example 1 is that no polydopamine modification is performed. The specific steps are:
[0074] Firstly, the aromatic polyamide membrane is immersed in a 10 mg / ml sulfated glycidyl ether solution containing 1 wt% triethanolamine for reaction at room temperature for 12 hours, then rinsed with deionized water and dried with nitrogen to obtain a polyglycidyl ether modified aromatic polyamide membrane;
[0075] Preparation of RO membrane filter element: The polyglycidyl ether modified aromatic polyamide membrane was immersed in a zwitterionic polymer aqueous solution and reacted at room temperature for 24 hours, then rinsed with anhydrous ethanol and dried with nitrogen to obtain a RO membrane filter element.
[0076] Comparative Example 3
[0077] The difference from Comparative Example 2 is that no zwitterionic polymer modification is performed, and the specific steps are as follows:
[0078] The aromatic polyamide membrane was immersed in a 10 mg / ml sulfated glycidyl ether solution containing 1 wt % triethanolamine and reacted at room temperature for 12 h, then rinsed with deionized water and dried with nitrogen to obtain a RO membrane filter element.
[0079] Performance testing
[0080] 1. Anti-pollution performance test
[0081] Three samples were taken from each of Examples 1 to 6 and Comparative Examples 1 to 3, and then a sodium chloride-bovine serum albumin solution was used as a feed solution, wherein the sodium chloride concentration was 5 mg / ml and the bovine serum albumin concentration was 0.5 mg / ml, and a permeation test was performed at 20 bar for 10 hours;
[0082] The permeation flux 10 minutes before the test was defined as the original flux, and the permeation flux 10 minutes after 10 hours was defined as the test flux. Finally, the flux decline rate was calculated to characterize the anti-pollution performance, and the average value was taken.
[0083] Flux decrease rate = (original flux - test flux) / original flux × 100%.
[0084] 2. Durability test
[0085] Three samples were taken from Examples 1 to 6 and Comparative Examples 1 to 3, respectively, and then the samples were tested one hundred times with reference to the above anti-pollution performance test. A flushing operation was performed before each test. Finally, the difference between the flux decrease rate at the first time and the flux decrease rate at the hundredth time was calculated, recorded as the durability rate, and the average value was taken.
[0086] The test data are shown in Table 3.
[0087] Table 3 Test data table of Example 1-Example 6 and Comparative Example 1-Comparative Example 3
[0088] Flux decline rate / % Durability / % Example 1 15.3% 4.9% Example 2 16.6% 5.1% Example 3 17.0% 5.2% Example 4 11.2% 3.8% Example 5 12.9% 4.1% Example 6 12.4% 4.3% Comparative Example 1 68.4% / Comparative Example 2 26.7% 10.1% Comparative Example 3 46.9% 11.5%
[0089] With reference to Example 1 and Comparative Examples 1 to 3 and in combination with Table 3, it can be seen that, relative to Example 1, the flux reduction rate and durability of Comparative Examples 1 to 3 are significantly improved, among which, relative to Comparative Example 1, the flux reduction rate and durability of Comparative Example 3 are significantly reduced, and the flux reduction rate and durability of Comparative Example 2 are further reduced.
[0090] This shows that the setting of sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating can effectively improve the anti-fouling performance and durability of RO membrane, and both polydopamine modification and zwitterionic polymer modification have a certain influence on the anti-fouling performance and durability of RO membrane.
[0091] The reason is that sulfated polyglycidyl ether is a polymer with a three-dimensional dendritic structure, which has excellent hydrophilicity, good protein and bacteria repellency, excellent thermal stability and excellent chemical stability. Therefore, when sulfated polyglycidyl ether is deposited on the RO membrane, the RO membrane will have extremely good anti-biological pollution performance. However, when sulfated polyglycidyl ether is deposited on the RO membrane, its anti-inorganic pollution performance is still insufficient.
[0092] The attachment of inorganic pollutants on the surface of RO membrane is mainly caused by the hydrophobic-hydrophobic interaction between the membrane and the pollutants. Therefore, hydrophilic modification of RO membrane is one of the important methods to improve the anti-fouling performance of RO membrane. Zwitterionic polymer is a polymer containing both positively charged and negatively charged groups. The hydrophilic groups it contains can form hydrogen bonds in water and interact with water molecules to obtain extremely good hydrophilicity. Therefore, when zwitterionic polymer is deposited on RO membrane, RO membrane will have extremely good anti-fouling performance.
[0093] However, both sulfated polyglycidyl ether and zwitterionic polymer have relatively poor connection effects with aromatic polyamide membranes, resulting in a short anti-fouling performance of RO membranes. Polydopamine coating has the advantages of simple preparation, wide applicable substrate range and strong adhesion ability, and polydopamine can also be co-deposited with zwitterionic polymers, thereby stably connecting zwitterionic polymers to the surface of aromatic polyamide membranes, and sulfated polyglycidyl ether can be grafted onto polydopamine coatings through Michael addition reaction, thereby forming a stable sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating on the aromatic polyamide membrane.
[0094] At the same time, during the long-term use of the RO membrane, micro-damage to the polydopamine coating is likely to lead to further adhesion and proliferation of pollutants, and enabling the polydopamine coating to have a self-healing function can effectively improve the above problems.
[0095] Self-repairing includes autonomous self-repairing and non-autonomous self-repairing. Autonomous self-repairing does not require any additional external triggers. The destruction itself is the stimulus for self-repairing, and the repair process is carried out autonomously within the material structure. In order to enable the polymer to form a self-repairing function, non-covalent bonds such as hydrogen bonds, ionic interactions or metal-ligand interactions and reversible covalent bonds such as disulfide bonds or acylhydrazone bonds are usually introduced into the polymer. The sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating has reversible covalent disulfide bonds and non-covalent hydrogen bonds and ionic interactions, which enables the sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating to have certain self-repairing properties, thereby obtaining better durability.
[0096] Referring to Example 1-Example 3 and combining with Table 3, it can be seen that compared with Example 1, the flux reduction rate and durability of Examples 2-3 are significantly improved, which shows that when the concentration of dopamine hydrochloride Tris buffer, sulfated glycidyl ether solution and zwitterionic polymer aqueous solution is the same as that of Example 1, the prepared RO membrane will have better anti-fouling performance and durability.
[0097] Referring to Example 1 and Example 4 and combining with Table 3, it can be seen that compared with Example 1, the flux reduction rate and durability of Example 4 are further reduced, which shows that the addition of gallium nitrate and ammonium persulfate can further improve the anti-pollution performance and durability of the RO membrane.
[0098] The reason is that during the preparation of the sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating, the polydopamine coating has the defect of slow deposition speed. After adding gallium nitrate and ammonium persulfate, the ammonium persulfate first decomposes rapidly under the catalysis of gallium ions to produce SO 4- Free radicals, SO 4- Free radicals further accelerate the oxidative polymerization of dopamine and increase the deposition rate of polydopamine, thereby achieving rapid preparation of polydopamine coatings, and obtaining more stable sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coatings. At the same time, the loading of gallium ions also promotes the sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coatings to obtain better antibacterial properties, ultimately showing better anti-fouling properties. And it may be due to the further addition of metals, thereby obtaining more ionic interactions, thereby obtaining better self-healing properties.
[0099] Referring to Example 4-Example 6 and combining with Table 3, it can be seen that compared with Example 4, the flux reduction rate and durability of Example 5-Example 6 are significantly improved, which shows that when gallium nitrate and ammonium persulfate are added in the amounts of Example 4, the prepared RO membrane will have better anti-pollution performance and durability.
[0100] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A ro membrane filter element, characterized in that The invention is an aromatic polyamide membrane with a sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating deposited on the surface.
2. The RO membrane filter element according to claim 1, characterized in that: The sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating is formed by the reaction of dopamine hydrochloride, sulfated polyglycidyl ether and zwitterionic polymer, and the mass ratio of dopamine hydrochloride, sulfated polyglycidyl ether and zwitterionic polymer is 1 (4-6):
1.
3. The RO membrane filter element according to claim 2, characterized in that The preparation method of the sulfated glycidyl ether comprises the following steps: Preparation of polyglycidyl ether: 170-190 mg 1,1,1-tri(hydroxymethyl)ethane, 20-30 mg sodium formate and 1-3 ml anhydrous methanol are stirred at room temperature for 1-3 h, 1,1,1-tri(hydroxymethyl)ethane is deprotonated by 10%, and then methanol is removed under vacuum at 70-90° C., then 30-50 ml 1,4-dioxane is added, ultrasonic dispersion is performed, argon is introduced to remove dissolved oxygen, and then 15-25 ml of a mixture of glycidol and 1,4-dioxane is slowly dripped in, the volume ratio of glycidol to 1,4-dioxane is 1:1, and after the dripping is completed, the reaction is continued at 90-110° C. for 12 h. After the reaction is completed, it is first cooled to room temperature, 1,4-dioxane is poured out, methanol is added to dissolve the polymer, the polymer is precipitated with excess n-hexane, and then vacuum dried to obtain polyglycidyl ether; Preparation of α-lipoic acid-polyglycidyl ether: 8-10 g of polyglycidyl ether was dissolved in 50-70 ml of N,N-dimethylformamide, and then 0.7-0.9 g of α-lipoic acid, 0.7-0.8 g of 4-(N,N-dimethylamino)pyridine and 0.7-0.9 g of N,N'-dicyclohexylcarbodiimide were added in turn under ice bath conditions, and reacted at room temperature for 35 h. The crude product was then precipitated with ether and dialyzed, and lyophilized to obtain α-lipoic acid-polyglycidyl ether; Preparation of sulfated glycidyl ether: 5-7g α-lipoic acid-polyglycidyl ether is dissolved in 40-60ml N,N-dimethylformamide, and then 13-15g aminosulfonic acid is added, and the reaction is carried out at 80-100°C for 72h. Subsequently, the crude product is precipitated out by ether and dialyzed. After freeze-drying, 12-13g of the product is dissolved in 90-110ml deionized water, and argon is passed for 30min. Then 400-500mg DL-dithiothreitol is added, and the reaction is carried out at 40-60°C for 24h. Finally, it is dialyzed and lyophilized to obtain sulfated glycidyl ether.
4. The RO membrane filter element according to claim 2, characterized in that The preparation method of the zwitterionic polymer is as follows: 0.05-0.15g of chitosan is dissolved in 30-50ml of 1% acetic acid solution, then heated to 50-70°C while introducing nitrogen, 20-30mg of ammonium persulfate initiator and 0.4-0.6g of 2-methacryloyloxyethyl phosphorylcholine are added in sequence, the reaction is continued at a temperature of 50-70°C for 12h, then cooled to room temperature, dialyzed, concentrated and freeze-dried to obtain the zwitterionic polymer.
5. The RO membrane filter element according to claim 1, characterized in that: Gallium nitrate and ammonium persulfate are added during the preparation of the sulfated polyglycidyl ether-polydopamine-zwitterionic polymer coating.
6. The RO membrane filter element according to claim 5, characterized in that: The mass ratio of the gallium nitrate to ammonium persulfate is 1:(3-5).
7. A method for preparing a RO membrane filter element according to any one of claims 1 to 6, characterized in that: The following steps are involved: Polyglycidyl ether-polydopamine modification: first, the aromatic polyamide membrane is immersed in a Tris buffer solution of dopamine hydrochloride, reacted at room temperature for 3-5 hours, taken out, blown dry with nitrogen, and then immersed again in a sulfated glycidyl ether solution containing 1wt% triethanolamine and reacted at room temperature for 10-14 hours, then rinsed with deionized water, blown dry with nitrogen, to obtain a polyglycidyl ether-polydopamine modified aromatic polyamide membrane; Preparation of RO membrane filter element: soak the polyglycidyl ether-polydopamine modified aromatic polyamide membrane in a zwitterionic polymer aqueous solution and react at room temperature for 20-28 hours, then rinse with anhydrous ethanol and blow dry with nitrogen to obtain a RO membrane filter element.
8. The method for preparing a PD membrane filter element according to claim 7, characterized in that: The concentration of the Tris buffer of dopamine hydrochloride is 1.8-2.2 mg / ml; the concentration of the sulfated glycidyl ether solution is 9-11 mg / ml; and the concentration of the zwitterionic polymer aqueous solution is 1.8-2.2 mg / ml.
9. The method for preparing a PD membrane filter element according to claim 7, characterized in that: The specific steps of the polyglycidyl ether-polydopamine modification are: First, 5-7 mg of ammonium nitrate and 23-25 mg of ammonium persulfate are added to 5 ml of Tris buffer containing dopamine hydrochloride at a concentration of 1.8-2.2 mg / ml, and then the aromatic polyamide membrane is immersed in the above solution, reacted at room temperature for 3-5 hours, taken out, blown dry with nitrogen, and then immersed again in a sulfated glycidyl ether solution containing 1 wt% triethanolamine at a concentration of 9-11 mg / ml and reacted at room temperature for 10-14 hours, then rinsed with deionized water, blown dry with nitrogen to obtain a polyglycidyl ether-polydopamine modified aromatic polyamide membrane.
Citation Information
Patent Citations
Method for preparing pressure retarded osmosis membrane modified by zwitterionic random copolymer
CN110354692A
Ga<3+> / PDA targeted co-antibacterial nanometer material, and preparation and application thereof
CN110787186A
Antibacterial / lubricating dual-function coating as well as preparation method and application thereof
CN118320182A